Remodeling of nuclear landscapes during human myelopoietic cell differentiation maintains co-aligned active and inactive nuclear compartments - Markaki, Yolanda (2015)
Background: Previous studies of higher order chromatin organization in nuclei of mammalian species revealed both structural consistency and species-specific differences between cell lines and during early embryonic development. Here, we extended our studies to nuclear landscapes in the human myelopoietic lineage representing a somatic cell differentiation system. Our longterm goal is a search for structural features of nuclei, which are restricted to certain cell types/species, as compared to features, which are evolutionary highly conserved, arguing for their basic functional roles in nuclear organization.